Pengaruh Karakteristik Individu dan Lingkungan Kerja Terhadap Kinerja Karyawan: Studi Kasus pada PT Pelabuhan Indonesia Regional 2 Panjang - Dunan, Hendri; Abdullah, Agra Adiyasya (Jurnal EMT KITA, 2024)
This research aims to examine the influence of individual characteristics and the work environment on employee performance at PT Pelabuhan Indonesia Regional 2 Panjang. Using quantitative methods, this research collected data from 154 employees, representing 25% of the total population. Primary data obtained through direct surveys uses instruments that have been tested for validity and reliability. Data analysis was carried out using multiple linear regression techniques using SPSS software. The research results show that there is a significant simultaneous influence between individual characteristics and the work environment on employee performance. These findings provide new insight into the factors that influence performance in work environments such as PT Pelabuhan Indonesia Regional 2 Panjang.